Teachers as Adult Learners: Their need to Transform - Papathanasiou, Maria (Adult Education Critical Issues, 2023)
In today's school, it is no longer the abundance of knowledge that matters, but the methods of acquiring it, the cultivation of skills, and the preparation of students to become active citizens and not just observers. The rapidly changing social environment and lately the Pandemic, have further elevated the role of education by introducing, if not "mandating", lifelong learning for the overwhelmed teachers. Considering the importance and criticality of the school's mission, the importance of the teacher's duties and the challenge in the implementation of their work can easily be seen. In this article, we will briefly explore three of the most basic theories of adult education and significant aspects of constructivism, whose tenets also undergird, teachers’ continuous and imperative need of adults’ lifelong learning. The theories discussed are the Andragogy of Knowles, Freire’s educational Social Change, and Mezirow’s Transformation Theory, as a resource for deepening our understanding of the critical matters affecting the need for new ways for teachers to approach their learning and teaching.